2018
DOI: 10.18559/ebr.2018.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Different sources of market information and product innovativeness

Abstract: : The purpose of this study is to identify whether the gathering of market information from different sources -i.e. from customers, competitors and other entities -is related to product innovativeness. The relationships proposed so far have not been empirically investigated but they can have important theoretical and practical implications for product innovation. To achieve the purpose of the paper data concerning 287 new products were used by applying confirmatory factor analysis and structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Kongaut and Bohlin (2017) found that broadband speeds had a positive effect on the gross domestic product, and this effect was higher in lower-income countries. According to Dąbrowski (2018), market information received from consumers and businesses (excluding competitors) has a positive effect on product innovation. Kotowicz-Jawor (2019) analysed the relationship between the current developmental stage of the Polish economy and the determinants of its innovation potential in the context of the EU structural funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kongaut and Bohlin (2017) found that broadband speeds had a positive effect on the gross domestic product, and this effect was higher in lower-income countries. According to Dąbrowski (2018), market information received from consumers and businesses (excluding competitors) has a positive effect on product innovation. Kotowicz-Jawor (2019) analysed the relationship between the current developmental stage of the Polish economy and the determinants of its innovation potential in the context of the EU structural funds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Product innovation is what can be considered as a functional product advancement that is one step ahead of competing products. Products with added value benefits for consumers [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…People obtain knowledge from different sources depending on purposes for which they are searching for knowledge and their personal needs (Dąbrowski, 2018). These sources can vary depending on the problems which people want to go through or solve using this knowledge.…”
Section: Sources Of Knowledge That People Use and Prefer For Specific...mentioning
confidence: 99%